State Responsibility For Air Quality: Case Study Of Decision Number 374/Pdt.G/Lh/2019/Pn.Jkt.Pst Related To Citizen Lawsuit Over Air Pollution In Dki Jakarta And Surrounding Areas - Astarina, Oryza Trivia (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Air is an absolute necessity for human life and livelihood. The existence of pollution and damage to air quality will greatly impact humans in all areas of life. The Indonesian Constitution in Article 28H paragraph (1) guarantees the right of its citizens to obtain a good and healthy environment, so that mutatis mutandis this also raises the burden of state responsibility to fulfill it. Due to the occurrence of air pollution in the DKI Jakarta Province and surrounding areas that have disrupted the activities of citizens, the Ibukota Movement Advocacy Team (Inisiatif Bersihkan Udara Koalisi Semesta) filed its claim for healthy air with a citizen lawsuit mechanism. Through the Central Jakarta District Court Decision Number 374/PDT.G/LH/2019/PN.JKT.PST, the panel of judges decided that the government had committed an illegal act, so the state must be responsible for the air pollution that occurred